2021
DOI: 10.3390/w13131720
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Long-Term Connections between Trophic Status, Sestonic Chlorophyll, Nutrients, Organic Matter, and Monsoon Rainfall in a Multipurpose Reservoir

Abstract: Due to rapid eutrophication, sustainable water quality management and supply are essential in drinking water sources and aquatic biota in large reservoirs. We evaluated the potentially crucial factors influencing the algal chlorophyll (CHL-a), nutrients, and the links between the rainfall and other vital elements in a large multipurpose reservoir (Yongdam Reservoir) during 2013–2019. We developed the empirical models on algal CHL-a, total phosphorus (TP), total nitrogen (TN), and TN:TP’s ambient ratios conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The monthly decrease in TN was connected with the increase in monthly precipitation ( Figure 2 and Figure 3 ). The outcomes support the influence of ionic dilution on the nitrogen contents in connection with large amounts of rainfall [ 7 , 48 , 49 , 50 , 58 ]. The seasonal patterns of phosphorus contents (TP, TDP, PO 4 -P) in each zone showed no statistically significant differences.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The monthly decrease in TN was connected with the increase in monthly precipitation ( Figure 2 and Figure 3 ). The outcomes support the influence of ionic dilution on the nitrogen contents in connection with large amounts of rainfall [ 7 , 48 , 49 , 50 , 58 ]. The seasonal patterns of phosphorus contents (TP, TDP, PO 4 -P) in each zone showed no statistically significant differences.…”
Section: Resultssupporting
confidence: 60%
“…This is because the EC is sensitive to variations in dissolved solids, mainly mineral salts [ 10 ]. However, in non-estuarine reservoirs of Korea, an increasing trend of EC from Lz to Tz and to Rz was generally observed, as EC is more correlated with anthropogenic pollutants [ 45 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spring, the algal abundances indicated oligo-mesotrophic conditions; however, by summer, the trophic level of the water had increased significantly, and characteristic species showed eutrophic relations. Jargal et al [69] found that large macrovegetation coverage, water level fluctuation and nutrient enrichment are the most common water quality issues. With the arrival of fall, the trophic conditions decreased once again to a mesotrophic level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to control the high TP inflows and further investigate the phytoplankton species and their functional groups. This can be done by regulating the usage of P-yielding fertilizers and controlling industrial effluents to restrict nutrient inputs [25,80]. It is, therefore, crucial to locate the hotspots of high TP concentrations in the reservoir watershed and implement effluent standards based on individual points.…”
Section: Seasonal Trophic Status Assessmentmentioning
confidence: 99%